Pengembangan lembar kerja peserta Didik berbasis inkuiri terbimbing materi larutan penyangga kelas XI MA - Anti, Rezamedianty (Jurnal Riset Pendidikan Kimia (JRPK), 2022)
This research is an R & D (Research and Development) which aims to see the validity and responses of students to Student Worksheets based on guided inquiry on buffer solution materials. This research development procedure adopts the Borg and Gall models until the seventh stage. This study involved three validators, one validator, a media / design expert, and two material experts. Small and medium scale trial subjects were students of MA Nurul Huda Sukaraja. The data instrument used validation sheets, student response questionnaires, and new interviews. The results showed that the chemical LKPD based on tobacco inquiry on the buffer solution, the proportion of design experts / media was 85.41% with a very valid category, and the proportion of tenacity obtained from two material expert trainers was 98.29% with a very valid category. The proportion of the average value of the three validators is 88.98% with the very valid category. Student responses to the developed chemistry worksheet can be categorized as very interesting, where small-scale trials get a proportion of 96.72% with a very attractive category, in the medium-scale trial the proportion is 89.34% and is stated to be very interesting.Key words: LKPD, guided inquiry, buffer solution.